In-Smartive undergraduates help schools to master English - UMP, PNC
A total of 148 undergraduates took part in the ‘Kilauan Mutiara Teach Malaysia Teach’ (TMT) organised by Universiti Malaysia Pahang (UMP) In-Smartive Club aimed at strengthening the command in English among pupils in Pekan.